AUSTRALIA'S DEFENSE STRATEGY IN DEALING WITH POTENTIAL THREATS FROM CHINA IN THE ASIA PACIFIC REGION - Abyan Dhamar Averill (Dauliyah: Journal of Islam and International Affairs, 2024)
The AUKUS alliance, a three-way strategic defence partnership between Australia, the United Kingdom and the United States, was announced with the aim of building a nuclear submarine fleet. The research method used in this analysis is a qualitative approach, focusing on foreign policy studies and literature reviews related to geopolitical relations in the Asia-Pacific region. The author uses the concept of foreign policy to understand how the threat from China affects Australia's security strategy. The strategy aims to better position Australia to contribute to regional security and stability, as China’s increasing self-sufficiency and the risk of military conflict between major powers in the Indo-Pacific region increase. The document provides a grim assessment of security in the Pacific and sets out a massive increase in defence expenditures to restructure the Australian military to cope with the changing security environment in Asia-Pacific. The review also focuses on the operationalization of a deterrence by a denial strategy, which includes the acquisition of a more powerful and lethal long-range attack capability and the upgrading of Australian northern bases to force rotations. This strategy emphasizes the importance of suppressing China's "competitive tactics" through a combination of military capabilities, diplomacy and alliances with traditional partners.